- Implementasi Penilaian Keterampilan dalam Kurikulum Merdeka Belajar pada Pembelajaran Pendidikan Agama Islam - Rohmatin Nur Ifana, Siti; Hasanah, Muslimatul; Putri As-syafi’i, Rizka; Bashith, Abdul (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
Merdeka Curriculum is a new approach in the education system that provides freedom and flexibility to learners to choose and organize learning according to their needs and interests. Islamic Religious Education (PAI) as one of the important subjects in this curriculum also requires proper implementation of skills assessment to measure learners' abilities as to how far learners understand and apply religious principles in their daily lives. This research method uses library research which aims to explain the implementation of skills assessment in Merdeka Curriculum in Islamic Education learning. First of all, skills assessment in PAI learning must be based on the expected competencies. Skills assessment in the Merdeka Curriculum in PAI learning can be carried out through various relevant evaluation methods. These methods can include observation assessment, individual or group assignments, presentations, and projects.